The effects of low-frequency ultrasound and microbubbles on rabbit hepatic tumors. (June 2014) - Shen, Zhi-Yong; Xia, Gan-Lin; Wu, Ming-Feng; Shi, Min-Xin; Qiang, Fu-Lin; Shen, E; Hu, Bing
High-intensity focused ultrasound in combination with microbubbles (MBs) is able to inhibit the growth of VX2 rabbit liver tumors in vivo and prolong the survival time of the animals. In this study, we attempt to investigate the feasibility of VX2 tumor growth inhibition using low-frequency ultrasound (US)-mediated MB disruption. Forty-eight New Zealand rabbits with hepatic VX2 tumors were divided into four groups: control, MBs group, low-frequency US group, and US + MB group. The parameters of the US were 20 kHz, 2 W/cm 2, 40% duty cycle, 5 min, and once every other day for 2 weeks. At the end of the therapy experiment, 24 rabbits were euthanized, and the cancers were collected and cut into five sections for histological examination, immunohistochemistry, laser confocal microscopy, western blotting assays, and transmission electron microscopy (TEM). Another 24 rabbits were saved, and overall survival time was recorded. The tumor volumes in control, MB, US, and US + MB groups were 6.36 ± 0.58, 5.68 ± 0.42, 5.29 ± 0.26, and 2.04 ± 0.14 cm 3, respectively (US + MB versus the other three groups, P < 0.01). Tumor cells manifested coagulation necrosis with internal calcification. Hematoxylin and eosin (H–E) staining revealed interstitial hemorrhage and intravascular thrombosis. The intensity of cyclooxygenase-2 (COX-2), and vascular endothelial growth factor (VEGF) in the US + MB group in the immunohistochemical staining, laser confocal microscopy, and western blotting assays was lower than that of the other three groups ( P < 0.05). TEM of the US + MB group revealed vascular endothelial cell wall rupture, widened endothelial cell gaps, interstitial erythrocyte leakage, and microvascular thrombosis, while intact vascular endothelial cells and normal erythrocytes in the tumor vessels were observed in control, MB, and US groups. Rabbits treated with US + MB had a significantly longer overall survival than those in the other three groups (χ2 = 9.328, P = 0.0242). VX2 tumor growth could be inhibited by cavitation induced using low-frequency US and MB.